The Future of Banking in Europe - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2001)
At least in the past, banking in continental Europe has been characterised by a number of features that are quite specific to the region. They include the following: (1) banks play a strong role in their respective financial systems; (2) universal banking is prevalent; (3) not strictly profit-oriented banks play a significant role; and (4) there are considerable differences between national banking systems. It can be safely assumed that the future of banking in Europe will be shaped by three major external developments: deregulation and liberalisation; advances in information technology; and economic, financial and monetary integration. The overall consequences of these developments would be much too vast a topic to be addressed in one short paper. Therefore the present paper concentrates on the following question: Are the traditional peculiarities of the banking and financial systems of continental Europe likely to disappear as a consequence of the aforementioned external developments or are they more likely to remain in spite of these developments? The external developments affect the features specific to banking in continental Europe only indirectly and only via the strategies selected and pursued by the various players in the financial systems, notably the banks themselves, and in ways which strongly depend on the structure of the banking industry and the level of competition between banks and other providers of financial services. The paper develops an informal model of the relationships between (1) external developments, (2) bank strategies and the structure of the banking industry, and (3) the peculiarities of banking in Europe, and derives a hypothesis predicting which of the traditional peculiarities are likely to disappear and which are likely to remain. It argues that, overall, the peculiarities are not likely to disappear in the short or the medium term. – – Der vorliegende Beitrag stellt einen Versuch dar, die Zukunft des Bankwesens in Europa unter der spezifischen Fragestellung zu analysieren, ob sich trotz der offensichtlichen und gravierenden Änderungen informations-technologischer, regulatorischer und politischer Art im Umfeld der Banken die traditionellen Besonderheiten der kontinentaleuropäischen Banksysteme in der Zukunft erhalten oder ob sie in der Folge dieser Änderungen eher verschwinden werden. Zu diesen Besonderheiten gehören unter anderem enge Beziehungen zwischen Banken und ihren Kreditnehmern, eine starke Rolle von nicht oder nicht primär gewinnorientierten Banken und beträchtliche Unterschiede zwischen den Bank- und Finanzsystemen verschiedener Länder. Methodisch geht der Beitrag so vor, dass untersucht wird, wie Banken bei der Festlegung ihrer Strategien auf die Änderungen Art reagieren und wie sich dies auf den Wettbewerb im Bankwesen auswirkt, um daraus Schlüsse hinsichtlich des Fortbestehens bzw. des Verschwindens der angesprochenen traditionellen Besonderheiten von Banking in Europe zu ziehen. Es lässt sich zeigen, dass mindestens einige der traditionellen Besonderheiten – entgegen weit verbreiteten Erwartungen – zumindest mittelfristig nicht verschwinden werden.
urn:nbn:de:hebis:30-16763
Keywords: G15; G20; G21; P50; 330; Banking in Europe; bank strategies; competition in banking; disintermediation; financial systems; non-profit banking; universal banking; Finanzsystem; Institutioneller Wandel; Bankmanagement; Internationaler Wettbewerb; Lieferanten-Kunden-Beziehung; Universalbank; Europa